Analysis of an Undamped Mass-Spring System with Generalized Piecewise Constant Argument - Akhmet, Marat; Çinçin, Duygu Aruğaslan; Özkan, Zekeriya (Journal of Vibration Testing and System Dynamics, 2026)
In this study, we consider an undamped mass-spring system that experiences piecewise constant forces and analyze the solutions of this system. We investigate the solutions of undamped mass-spring system by using the method of steps. In addition to investigating the solutions, stability and convergency analyses are performed for the solutions of nonhomogeneous undamped mass-spring system. The results are stated in terms of the parameters of the systems. Simulations are given to illustrate and support the findings for different values of the parameters.